2008
DOI: 10.1175/2008jas2480.1
|View full text |Cite
|
Sign up to set email alerts
|

Inertia–Gravity Waves Emitted from Balanced Flow: Observations, Properties, and Consequences

Abstract: This paper describes laboratory observations of inertia-gravity waves emitted from balanced fluid flow. In a rotating two-layer annulus experiment, the wavelength of the inertia-gravity waves is very close to the deformation radius. Their amplitude varies linearly with Rossby number in the range 0.05-0.14, at constant Burger number (or rotational Froude number). This linear scaling challenges the notion, suggested by several dynamical theories, that inertia-gravity waves generated by balanced motion will be ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 46 publications
5
58
0
Order By: Relevance
“…This was because U 0 and H 0 are constant for the cases of fixed Fr, and an unsteady jet flow is qualitatively the same for all cases. The shift of the dominant source term, which agrees with a previous laboratory study (Williams et al 2005(Williams et al , 2008, may cause an amplification of the gravity wave flux for smaller Ro. It is probable that there is a lo- cal maximum in the gravity wave flux for the cases of smaller Fr for Ro ∼ 10.…”
Section: Analysis Of the Source Of Gravity Wavessupporting
confidence: 89%
“…This was because U 0 and H 0 are constant for the cases of fixed Fr, and an unsteady jet flow is qualitatively the same for all cases. The shift of the dominant source term, which agrees with a previous laboratory study (Williams et al 2005(Williams et al , 2008, may cause an amplification of the gravity wave flux for smaller Ro. It is probable that there is a lo- cal maximum in the gravity wave flux for the cases of smaller Fr for Ro ∼ 10.…”
Section: Analysis Of the Source Of Gravity Wavessupporting
confidence: 89%
“…On the other hand, a recent laboratory experiment (Williams et al 2008) showed that the amplitude changes linearly with Ro for Ro  1. Although the setting and the parameter range of the present paper are different from those of the studies mentioned above and the data shown in Fig.…”
Section: Summary and Discussionmentioning
confidence: 96%
“…Laboratory experiments of a two-layer system have been conducted to examine generation of gravity waves from vortical motions after Lovegrove et al (2000). In a parameter region of Ro  1, Williams et al (2005) and Williams et al (2008) showed that gravity waves are generated during the decay phase of the vacillation motions of the baroclonic wave and the amplitude of the generated gravity waves changes linearly with Ro. On the other hand, theoretical studies with highly idealized settings in this parameter region propose that the wave amplitude increases exponentially with Ro (Vanneste and Yavneh 2004;Plougonven et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It can only exist as a modified concept of so called slow quasi-manifold or fuzzy manifold (Lorenz, 1986(Lorenz, , 1987(Lorenz, , 1992Jacobs, 1991;Vautard and Legras, 1986;Vallis, 1996;Vanneste and Yavneh, 2004;Warn and Menard, 1986;Warn et al, 1995;Warn, 1997;Ford, 2000), which means that balanced flow, to some extent, is just an approximation except for some particular cases such as parallel geostrophic flows and axisymmetric gradient flows. There is also now strong experimental evidence that the slow manifold is not an invariant manifold (Williams et al, 2008).…”
Section: Basic State Vortical Flow Balance and Imbalancementioning
confidence: 99%